2016
DOI: 10.4103/0973-7847.176566
|View full text |Cite
|
Sign up to set email alerts
|

Review of naturopathy of medical mushroom,Ophiocordyceps sinensis, in sexual dysfunction

Abstract: Sexual dysfunctions including desire, arousal, orgasm, and pain disorders are increasing worldwide due to etiological factors and aging. Several types of treatment are claimed in modern medicine, but they have serious side effects and higher costs. In fact, alternative approaches, such as the intake of plants, fungi, and insects, or their extracts, have also been practiced to enhance sexuality and ameliorate illness with notable successes. However, the scientific evidence related to the mechanisms and efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…O. sinensis mainly inhabits the alpine meadow ecosystem of Qinghai-Tibetan Plateau, Sichuan, Yunnan and Gansu Provinces in China, also distributes in certain areas of Bhutan, Nepal and India [2]. As the well-known traditional Chinese medicinal herb, O. sinensis has been widely used for centuries in Asia, exhibit bene cial properties and remedy for a variety of chronic disorders, including asthma, cancer, sexual dysfunction, obesity, type 2 diabetes and fatigue, etc., presumably, by modulating the composition of gut microbiota [3][4][5][6]. O. sinensis harbour a variety of bioactive metabolites, e.g., cordycepin, cordycepic acid, polysaccharides, ergosterol, mannitol and macrolides, etc..…”
Section: Introductionmentioning
confidence: 99%
“…O. sinensis mainly inhabits the alpine meadow ecosystem of Qinghai-Tibetan Plateau, Sichuan, Yunnan and Gansu Provinces in China, also distributes in certain areas of Bhutan, Nepal and India [2]. As the well-known traditional Chinese medicinal herb, O. sinensis has been widely used for centuries in Asia, exhibit bene cial properties and remedy for a variety of chronic disorders, including asthma, cancer, sexual dysfunction, obesity, type 2 diabetes and fatigue, etc., presumably, by modulating the composition of gut microbiota [3][4][5][6]. O. sinensis harbour a variety of bioactive metabolites, e.g., cordycepin, cordycepic acid, polysaccharides, ergosterol, mannitol and macrolides, etc..…”
Section: Introductionmentioning
confidence: 99%
“…O. sinensis mainly inhabits the alpine meadow ecosystem of Qinghai-Tibetan Plateau, Sichuan, Yunnan and Gansu Provinces in China, also distributes in certain areas of Bhutan, Nepal and India [2]. As the well-known traditional Chinese medicinal herb, O. sinensis has been widely used for centuries in Asia, exhibit bene cial properties and remedy for a variety of chronic disorders, including asthma, cancer, sexual dysfunction, obesity, type 2 diabetes and fatigue, etc., presumably, by modulating the composition of gut microbiota [3][4][5][6]. O. sinensis harbour a variety of bioactive metabolites, e.g., cordycepin, cordycepic acid, decade, progressive studies have been devoted to isolate and identify fungal species from habitats of O. sinensis by culture-dependent approach.…”
Section: Introductionmentioning
confidence: 99%
“…The caterpillar fungus Ophiocordyceps sinensis parasitizes the larvae of Thitarodes that belong to family Hepialidae (Lepidoptera) distributed in the Qinghai-Tibetan Plateau and its adjacent areas, form the fungus-caterpillar complex (Chinese cordyceps) [1,2]. As the well-known traditional Chinese medicinal herb, O. sinensis has been widely used for centuries in Asia, exhibit bene cial properties and remedy a variety of chronic disorders, including asthma, cancer, sexual dysfunction, obesity, type 2 diabetes, fatigue, etc., presumably, by modulating the composition of gut microbiota [3][4][5][6]. O. sinensis harbour a variety of bioactive metabolites, e.g., cordycepin, cordycepic acid, polysaccharides, ergosterol, mannitol and macrolides, etc..…”
Section: Introductionmentioning
confidence: 99%
“…4). The UniFrac-weighted Principal Coordinate Analysis (PCoA) showed that JM-1, JM-2, JM-3 were clustered together, TY-2, TY-3, TY-4 were separated on other side, which revealed that there are signi cant differences in fungal community structure between external mycelial cortices (EMC) with soil microhabitat (Soil) (Figure.5).…”
mentioning
confidence: 97%